MANAGEMENT OF BULBUS OCULI PROLAPSE IN A CAT AT JOGJA VETERINARY CLINIC, YOGYAKARTA - Decline, Vega; Rizky, Asri; Viastika, Yanita Mutiaraning; Seruni, Puti Puspa; Wibowo, Sarwo Edy (VITEK : Bidang Kedokteran Hewan, 2025)
Enucleation is an orbital surgical procedure performed on patients with indications of increased intraocular pressure due to glaucoma that cannot be treated with medication, intraocular neoplasia that may cause intraocular pain, or severe trauma. Prolapse of the bulbus oculi in cats is generally caused by glaucoma (increased intraocular pressure), bacterial or viral infections, trauma from being hit by a vehicle, scratches, fights with other animals, or ocular tumors. The purpose of this report is to describe the management of enucleation in cats at Jogja Veterinary Clinic, Yogyakarta. The subject of this case is a female cat named Telon, approximately four months old, weighing 1.65 kg, who was brought to Jogja Veterinary Clinic with a complaint of a protruding eye. Based on anamnesis, physical examination, and clinical symptoms, Telon was diagnosed with bulbus oculi prolapse and underwent enucleation surgery as a medical intervention. The treatment provided included antibiotics, vitamins, analgesics, and topical ointment. The cat received postoperative care for four days and showed good wound healing. It was concluded that the enucleation procedure using the transpalpebral technique in Telon had a favorable prognosis. Keywords: Prolapse of the Bulbus Oculi, Cats, and Enucleation